The Bible in the North - Hannah M. Strømmen (Svensk Exegetisk Årsbok)
Understanding biblical texts in context usually entails an awareness of the times and places in which these texts first emerged and were first encountered. In this article, I aim to make a case for more contextual work on the Bible in the Northern parts of the contemporary world. After discussing context in relation to the Bible, I turn to the Global North and questions of secularization, before providing examples of the way the Bible operates as commodity and content on the secular marketplace in Norway. Rather than hyperlocal research into the details of Bible-use in regions that might be considered “the North,” I argue that analysing the Bible in the North requires attention to the way Bibles and biblical texts circulate and change as part of global flows.